How Egyptian social identity is represented in billboards: A linguistic analysis - El-Feky, Eman (AUC Knowledge Fountain, 2019)
This study aims to explore the use of language in 70 Egyptian billboards located in Greater Cairo in an attempt to investigate how Egyptian social identity is reflected in such billboards. The study proposes three research questions where the first one deals with the type of discursive strategies and grammatical structures that are mostly preferred by advertisers. The second research question seeks to investigate the pattern of code choice that are used by advertisers in relation to the type of product and the location of the billboard. The third research question investigates how Egyptian social identity is reflected through the use of language and the displayed images. The study utilizes the frameworks of discourse analysis, linguistic landscape (Landry and Bourhis, 1997), and multimodality (Kress and van Leeuwen, 2001; Kress, 2013) to investigate 70 billboards located in five different locations in Greater Cairo. The findings of the study show that advertisers depend on certain discursive strategies, such as presupposition, parallelism, dialogicality, and intertextuality to convey their messages to their customers. In addition, advertisers tend to rely on particular code choices to target different segments of the community. Egyptian social identity is reflected differently depending on the location of billboards and the type of product or service being advertised.